Friedreich Ataxia: current status and future prospects - Katrin Bürk (Cerebellum & Ataxias, 2017)
Abstract Friedreich ataxia (FA) represents the most frequent type of inherited ataxia. Most patients carry homozygous GAA expansions in the first intron of the frataxin gene on chromosome 9. Due to epigenetic alterations, frataxin expression is significantly reduced. Frataxin is a mitochondrial protein. Its deficiency leads to mitochondrial iron overload, defective energy supply and generation of reactive oxygen species. This review gives an overview over clinical and genetic aspects of FA and discusses current concepts of frataxin biogenesis and function as well as new therapeutic strategies.